The Significance of Mineral Nutrition on The Physical and Chemical Properties of Cellular Juice of Wormwood Leaves (Artemisia Leucodes Schrenk) - Pirakhunova F.N.; Shayusupova N.B (Zien Journals, 2022)
The research was carried out in order to study the importance of nitrogen and phosphorus fertilizers on the growth and development of plants, various forms of nitrogen fertilizers and the degree of phosphorus supply to the soil on the physicochemical properties of the cell sap of whitish wormwood leaves. It was revealed by authors that while cultivating whitish wormwood, the most effective form of nitrogen fertilization is urea, the main dose of which is applied to the soil in the phase of 3-4 true leaves. However, due to its slow action during this period, it is advisable to introduce 33% of the annual nitrogen norm in the form of ammonium nitrate. And changes in the values of pH, Eh and rH2 indicators during the growing season largely depend on the forms of nitrogen fertilizers used.
Keywords: nitrogen; phosphorus; mineral nutrition; degree of soil supply